Medicinal plants indicated for flu and colds in the South of Brazil - Marjoriê da Costa Mendieta; Rita Maria Heck; Silvana Ceolin; Andrieli Daiane Zdanski de Souza; Natália Rosiely Costa Vargas; Manuelle Arias Piriz; Anelise Miritz Borges (Universidade Federal de Goias, 2015)
We sought to know the medicinal plants used for flu and colds by farmers from the South of Rio Grande do Sul State and to compare it with scientific evidence. This descriptive study was conducted with 12 farmers living at Ilha dos Marinheiros, in the city of Rio Grande, Rio Grande do Sul, Brazil. We used descriptive analysis, comparing the results with the scientific literature. Thirteen plants were cited as used for cold and flu: Achyrocline satureioides, Allium sativum, Cinnamomum zeylanicum, Citrus limon, Citrus reticulata, Citrus sinensis, Gochnatia polymorpha, Illicium verum, Mentha piperita, Mikania sp., Ocimum selloi, Origanum majorana and Verbena sp. Results show popular knowledge meeting scientific evidence for most indications, seen that 84,6% of cited plants are in agreement with the literature. Thus, we emphasize the richness of popular knowledge, the need of its appreciation and constant approximation of health professionals to this knowledge, integrated with science.